A comparative survey of the RF-amide peptide superfamily - Karine Rousseau (Frontiers Research Topics, 2015)
The discovery, twelve years ago, that the RF-amide peptide kisspeptin, acting via GPR54, is essential for the onset of puberty and reproduction, has been a major breakthrough in reproductive physiology. It has also put in front of the spotlights RF-amide peptides and allowed to revive research on this superfamily. The first member of this family to be characterized, in 1977, was the cardioexcitatory peptide, FMRFamide, isolated from the ganglia of the clam Macrocallista nimbosa. Since then, a large number of these peptides, designated after their C-terminal arginine (R) and amidated phenylalaline (F) residues, have been identified in representative species of all major phyla. By means of phylogenetic analyses, the superfamily of RFamide peptides has been divided into five families in vertebrates: kisspeptin, QFRP (including 26RFa), LPXRFa (including GnIH and RFRP), PQRFa (including NPFF) and PrRP. Recent data reveal that SIFamide-type neuropeptides in protostomian invertebrates and SALMFamide-type neuropeptides in deuterostomian invertebrates share a common evolutionary origin with vertebrate LPXRFa and PQRFa. Interestingly, in invertebrates as in vertebrates, multiple genes, as well as multiple mature peptides, are often present in a single species, questioning the need for such diversity in term of function. Comparative studies on non-mammalian vertebrates and invertebrates allow major advances in the knowledge of the evolutionary history of the RF-amide peptide superfamily. Such phylogenetical studies also contribute to improve classification and nomenclature of both peptides and receptors. RF-amide peptides from different families have major evolutionary conserved roles in the control of reproduction, but also of food intake, metabolism, energy expenditure, cardiovascular function, nociception and stress. They are also involved in the integration of environmental signals, notably the photoperiod, to regulate reproduction. For instance, in most vertebrate species and especially in seasonal mammals, kisspeptin and GnIH/RFRP have complementary but opposite effects in the control of reproductive function. In addition, recent data show cross-activities between the members of the RF-amide peptide superfamily and their receptors. For example, PrRP, kisspeptin and 26RFa are able to modulate nociception via NPFF receptors. Comparative studies have the potential to reveal novel regulatory mechanisms that could give a better comprehension of physiological functions and lead to new therapeutic treatments for related human pathologies. Thus, kisspeptin antagonists have been developed as novel tools for treatment of hormone-dependent disorders of reproduction such as precocious puberty and endometriosis or kisspeptin agonists for treatment of infertility, in humans. Studies on lower vertebrate models can also contribute to the discovery of new roles of these peptides, as seen recently with kisspeptin being involved in the early development of the medaka. This research topic will aim at gathering major advances achieved through comparative studies in (mammalian and non-mammalian) vertebrates and invertebrates, in the knowledge of RF-amide peptides in term of evolutionary history and physiological roles.